PERSEPSI MASYARAKAT TERHADAP PRAKTIK PERKAWINAN DINI DI SUKABUMI JAWA BARAT - Susanto, Susanto (Jurnal Aspirasi, 2012)
This paper aims at explaining some factors that led to the practice of under age marriage in Sukabumi West Java. Using qualitative research methods, it was found that the five factors are: the perception on puberty term, sustenance perception, the perception of the age limit of marriage, perceptions about who is morei deal to get married first, and perceptions to reduce the economic burden of the family. In addition, the practice of under age marriage that occurred are followed by a variety of issues such as: gender discrimination, divorce, lack of family stability, and parenting mistake. The practice of under age marriage is also reinforced by factors such as religious textualism and cultural interpretations adopted by the community.